Understanding intrinsic elements from drama text with cooperative learning method type STAD - Yunni Damayanti; Atmazaki Atmazaki; Ngusman Abdul Manaf (Fakultas Ilmu Pendidikan UNP)
This research is done to describe the process, result and increasing factors of students’ ability in understanding the intrinsic elements from drama text by using cooperative learning method type STAD of grade VIII.3 of Tri Bhakti Junior high school students Pekanbaru. The conclusion are; first, in the increasing process, teacher explain the learning target, explain the learning material, read student with the highest score to become group’s chairman, teacher monitored the learning process, then students come back to their own chair and answer the questions given by the teacher. Second, the students’ ability in understanding the intrinsic elements from drama text increase, from 64 in pre-cycle become 72.68 in cycle I then there is an increasing score in cycle 2 with average score 88.82. Third, Factors cause the increasing students’ ability in understanding the intrinsic elements of drama text are; chairman is responsible to the group work in order to understand the material and answer the questions related to elements of drama text that is explained, and students can explained in front of the class with good and correct language.